Agama Dan Iptek: Refleksi dan Tantangannya dalam Mengembangkan Moralitas Kaum Muda - Ch. Suryanti (Jurnal Orientasi Baru, 2010)
Younger generation holds a very important role in the development of science. Indeed, the fast-growing science has positive and negative effects on them. And, many young people lean on the mainstream view, embracing a hedonistic, pragmatic, and consumptive lifestyle. On the other hand, as a reaction, not few of them have involved in a new spiritual movement that tries to demonstrate that human existence is more than the fulfillment of physical needs, and that religion has important contribution in meeting spiritual needs. The question here is what are the roles of religion and science in transforming youth morality as integrated person, especially when some believe that religion is incompatible with science, and some other even blame the fast-growing science as the main cause of moral crisis among the youths.